Performa Produksi Domba yang Diberi Silase Komplit - Jama'Ahni Jama'Ahni; Padang Hamid; Sirajuddin Abdullah (Universitas Tadulako, 2019)
This study conducted to determine the influence of completed ration silage on production, performance and sheep physiological status. This study was conducted from March until June 2017. The was study arranged on Block Randomized Design with 4 treatments and repeated 6 times. The treatments are: 1. Maize forage fermented with EM4 2.maize forage silage. 3.grass king fermented with EM4 4. grass king silage. Silage composition was a analyzed for crude protein and crude fiber. Sheep performance (weight gain, dry matter consumption and ransum efficacy) and sheep physiological status (body temperature, respiration frequency and pulsus frequency) were measured. The results showed an increase in crude protein content and decrease of crude fiber content in fermented feed for all treatments. Complete of ration silage feeding gave significant effect on dry matter consumption (P <0,05), weight gain, and feed efficiency (P <0,01) but no significant effect on sheep physiological status (body temperature, respiration frequency and pulsus frequency).